Joining of β-γ TiAl alloys containing high content of niobium by pulse current diffusion bonding. (June 2021) - Gao, Qiang; Wang, Zeming; Zhang, Laiqi; Ge, Gengwu
Abstract: Spark plasma sintering was used to bond β-γ TiAl alloys containing high content of niobium. The microstructure features and recrystallization of bonding interface were investigated. The results showed that sound joint could be obtained through pulse current diffusion bonding (PCDB) conducted at 1150 °C under the applied pressure of 10 MPa for 20 min. The formation of α2 phase in the bonding interface can be suppressed at high temperature through PCDB compared with hot pressing diffusion bonding. The dynamic recrystallization mechanism in the bonding interface was discontinuous dynamic recrystallization through PCDB. The highest shear strength was 394.8 MPa at 1150 °C/10 MPa/20 min through PCDB. With bonding temperature increasing, intercrystalline fracture decreased and cleavage fracture increased on the fracture surface. Highlights: β-γ TiAl alloy containing high content of niobium was first diffusion bonded by pulse current diffusion bonding (PCDB). Oxide layer removed by micro-arc and spark was confirmed in PCDB. Dynamic recrystallization mechanism in the bonding interface was analyzed by EBSD.